Analisis Jurnal Internasional Kepuasan Kerja Karyawan - Prabowo, Budi; Samsudin, Acep; Sandiyudha, Dawam Sahrin Najah; Angelyta, Dosma; br Regar, Joy Verna Detta (Peneliti.net, 2024)
Employee job satisfaction is a way for someone to show that they love their job. The reasons why someone can love their job are supported by many factors such as the work environment, salary and compensation, emotional relationships between workers, gender, etc. This attitude can also reflect work morale, discipline, and work performance. Someone will feel at home and like their job if there is something that makes them happy, be it from salary, compensation, facilities, etc. This employee job satisfaction can also not only be felt by an individual but can also be felt by others, even consumers. Although an employee's job satisfaction has many supporting factors, there are also many factors that make the employee uncomfortable in their work environment such as uncomfortable work environment, low salary, not getting bonus money, etc. This study uses quantitative research, which is conducted by analyzing several international journal sources on employee job satisfaction. It is hoped that this analysis can be used as a study material on employee job satisfaction in the future.